Implementation Of Legal Protection For Women Victims Of Domestic Violence From A Human Rights Perspective - Diki Sahbana; Rehan suryananda; M.Fariz Kurnadi; Endang Sutrisno; Agus Dimyati (Edunity Kajian Ilmu Sosial dan Pendidikan, 2024)
The Indonesian government signed a declaration on the Elimination of Violence Against Women (1993) in 2014. However, at a technical level, violence against women still often occurs due to Domestic Violence (KDRT) in Indonesia. The purpose of this writing is to understand the implementation of laws and the protection of women's human rights against domestic violence from the perspective of international law. The research results show that the entry of the public law system into the domestic realm, namely domestic life, is one of the new developments in the field of human rights, especially in Indonesia. Domestic Violence (KDRT) has become a common agenda in the last few decades. The facts show that domestic violence has quite a negative effect on women as victims. The research that has been carried out is normative legal research which is focused on norms and also legal objects as the main data, and a book consisting of rules, and the truth of the research that has been carried out. All forms of violence have violated human rights as regulated in Law No. 23 of 2004 concerning the elimination of domestic.